已知初值条件\( y(0) = 1 \),则此时\( y' + y = {x^2}{e^{ - x}} \)的通解中常量\( C = \)( )。______
举一反三
- 已知初值条件\( y(0) = - 4 \),则方程\( y' + 5y = - 4{e^{ - 3x}} \)的通解中常量\( C = \)( )。______
- 方程\( y' + {y \over x} = {1 \over { { x^2}}} \)在\( y(1) = 0 \)时可得通解中常量\( C = \)( )。______
- 已知齐次方程$(x-1){{y}^{''}}-x{{y}^{'}}+y=0$的通解为$Y={{C}_{1}}x+{{C}_{2}}{{e}^{x}}$,则方程$(x-1){{y}^{''}}-x{{y}^{'}}+y={{(x-1)}^{2}}$的通解是( ) A: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{2}}+1)$ B: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{3}}+1)$ C: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}$ D: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}+1$
- 已知E(X)=2,E(Y)=2,E(XY)=5,则X,Y的协方差Cov(X,Y)=( )。 A: 1 B: 0 C: -1 D: 4
- 方程$(x^2+1)(y^2-1) + xy y' = 0$的通解为 A: $y^2 = C \frac{e^{-x^2}}{x^2}$ B: $y = C \frac{e^{-x^2}}{x^2}$ C: $y^2 = C \frac{e^{-x^2}}{x^2}+1$ D: $y=C \frac{e^{-x^2}}{x^2}+1$